STATUS OF CHILDREN OF AHMADIYYA MARRIAGE BASED ON THE PERSPECTIVE OF ISLAMIC SHARIA AND LAW NO. 1/1974 - Ahmad Hawasyi; Taufik Taufik (SEIKAT: Jurnal Ilmu Sosial, Politik dan Hukum, 2023)
This research focuses on the status and position of children resulting from marriages between Muslim women and Ahmadiyya men or vice versa. In terms of Islamic law, the Indonesian Ulama Council said that the Ahmadiyya sect is not a Muslim religion. If Ahmadis marry Muslim women, it will have implications for the status of their children, namely the status of children from marriages with Ahmadiyya from the perspective of the Islamic Shari'at Court with positive law. In this case the positive law in Indonesia indirectly gives magnitude norms so that it has an impact on the status of interfaith marriages so that all children born from these marriages, their civil relations must be registered with the civil registry. Thus, this shows that the civil rights of children out of wedlock which have implications for civil rights, nafaqah (living expenses), guardianship, and inheritance, are obtained from the father and his father's family as long as these problems only apply to same-religious marriages. As for civil rights to children out of wedlock who are not based on out of wedlock such as the result of adultery, incest, living together and the like or even interfaith marriages, the civil rights are only for the mother and the mother's family.